HYGIENIC ASSESSMENT OF WORKING CONDITIONS AND DEVELOPMENT OF MEASURES TO IMPROVE HEALTH AT COTTON PROCESSING ENTERPRISES - Самадова Х. С. (Bright Mind Publishing, 2025)
The article briefly discusses the issues of hygienic assessment of working conditions at the enterprises of the cotton processing industry and the development of comprehensive measures for their improvement.
Keywords: Citizen, country, society, enterprise, qualification, competitiveness.